Bodies, Sex and Desire from the Renaissance to the Present - Fisher, Kate. author. aut Link
XII, 275 p.
Keywords: An examination of how bodies and sexualities have been constructed, categorised, represented, diagnosed, experienced and subverted from the fifteenth to the early twenty-first century. It draws attention to continuities in thinking about bodies and sex: concept may have changed, but hey nevertheless draw on older ideas and language.